The mega-structure at Stăuceni-‘Holm’, Botoşani county, Romania and the debate about the governing of Cucuteni-Trypillia-settlements - Doris Mischka; Carsten Mischka; Adela Kovács; Constantin Aparaschivei; Elena Marinova (PLoS ONE, 2026)
2021 to 2024, the Cucuteni A3 settlement of Stăuceni-‘Holm’, Botoşani County in north-east Romania was surveyed geophysically and by systematic field collections. According to the geomagnetic results, on the plateau a settlement with about 45 houses was delimited by several ditch- and palisade systems. A comparatively large building (350 m 2 ) was located in the area between the ditches, which is meant to be a mega-structure, mainly due to its size and the clearly visible position next to the probable entrance of the settlement. The mega-structure was partially excavated in 2023–2024. The observations, regarding the architecture and the dating of the feature in particular, provide valuable information for the discussion about the function of these special structures, of which only five others have been investigated in detail by excavation to date.